Bevacizumab‐Laden Nanofibers Simulating an Antiangiogenic Niche to Improve the Submuscular Stability of Stem Cell Engineered Cartilage. Issue 23 (12th May 2022) - Zhu, Xinsheng; Xu, Yong; Xu, Xiaoxiong; Zhu, Junjie; Chen, Linsong; Xu, Yawen; Yang, Yang; Song, Nan
Abstract: Bone marrow stem cells (BMSCs) engineered cartilage (BEC) is prone to endochondral ossification in a submuscular environment due to the process of vascular infiltration, which limits its application in repairing tracheal cartilage defects. Bevacizumab, an antitumor drug with pronounced antiangiogenic activity, is successfully laden into a poly(L‐lactide‐co‐caprolactone) system to prepare bevacizumab‐laden nanofiber (BevNF) characterized by 5% and 10% bevacizumab concentrations. The in vitro results reveal that a sustained release of bevacizumab can be realized from BevNF, exhibiting inhibitive cytotoxicity toward human umbilical vein endothelial cells whereas non‐cytotoxicity toward BMSCs‐induced chondrocytes. A model is also established by encapsulating BEC within BevNF, aiming to realize an antiangiogenic niche under conditions of sustained and localized release of bevacizumab to inhibit the process of vascular invasion, resulting in the eventual stabilization of the cartilaginous phenotype and promotion of the process of cartilage maturation in the submuscular environment. These results also confirm that the chondrogenesis stability of BEC increases with an increase in the bevacizumab concentration, and 10% BevNF is sufficient to protect BEC from vascularization. This demonstrates that the use of BevNF can potentially help develop an effective strategy for regulating the submuscular stability of BEC to repair the defects formed in tracheal cartilage. Abstract : A bevacizumab‐laden nanofiber (BevNF) with pronounced antiangiogenic activity is successfully prepared. A model is established by encapsulating bone marrow stem cells engineered cartilage within BevNF, realizing an antiangiogenic niche under conditions of sustained and localized release of bevacizumab to inhibit the process of vascular invasion, resulting in the eventual stabilization of the cartilaginous phenotype and promotion of cartilage maturation in the submuscular environment.